LI-RADS® algorithm: CT and MRI - Chernyak, Victoria; Santillan, Cynthia S.; Papadatos, Demetri; Sirlin, Claude B. (Abdominal imaging, 2018)
The Liver Imaging Reporting and Data System (LI-RADS ® ) is an imaging-based diagnostic system applicable in patients at high risk of hepatocellular carcinoma (HCC). In LI-RADS, each liver observation is assigned a category that reflects probability of benignity, HCC, or other malignancy. Familiarity with the LI-RADS diagnostic algorithm is necessary to appropriately implement LI-RADS in clinical practice. This review discusses steps necessary for application of the LI-RADS algorithm and provides examples illustrating each step.